Liquid resin composition and resin-sealed power module
By using a low viscosity liquid resin composition, including epoxy resin, acid anhydride, curing accelerator and anti-settling agent, the problems of insufficient heat resistance of sealing materials at high temperatures and the settlement of inorganic filler materials are solved, and high heat resistance is achieved and excellent injection-molding operation, improving the overall performance of the device.
Patent Information
- Application Number
- CN202380044398.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-06
- Filing Date
- 2023-05-26
- Publication Date
- 2025-01-14
AI Technical Summary
The existing sealing materials are insufficient in heat resistance when used at high temperatures, which can easily lead to expansion and cracking, and the settlement of inorganic filler materials leads to reduced device reliability.
A liquid resin composition is adopted, including epoxy resin, acid anhydride, curing accelerator, inorganic filler material and anti-settling agent, with low viscosity and reduced settlement of inorganic filler material, and is used to seal the power module through injection molding method to improve heat resistance and injection molding operability.
The excellent injection molding operation and high heat resistance of the low viscosity liquid resin composition are achieved, and the crack resistance, electrical characteristics, mechanical characteristics and heat resistance of the cured product are significantly improved, reducing the reliability risk of the device.
Smart Images

Figure BDA0005164627170000181 
Figure BDA0005164627170000191 
Figure BDA0005164627170000201
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid resin composition and a resin-sealed power module. More specifically, the present invention relates to a liquid resin composition for injection molding for sealing a power semiconductor element and a power module manufactured using the same. Background Art
[0002] Epoxy resins are excellent in heat resistance, chemical resistance, insulation properties, etc., and are used as liquid sealing materials for injection molding to seal substrates and semiconductor elements in semiconductor devices.
[0003] In recent years, power semiconductor devices that can operate at high temperatures have been developed, and epoxy resins used as sealing materials for these devices are also required to have a higher level of heat resistance.
[0004] In addition, for sealing materials for power modules, low linear expansion is required in addition to insulation and heat resistance. This is to prevent cracking or peeling of the sealing resin caused by expansion due to heat generated from the power semiconductor element. In order to reduce the linear expansion coefficient, inorganic fillers are usually added to the sealing resin (for example, Patent Document 1).
[0005] However, the addition of inorganic fillers may sometimes increase the viscosity of the sealing material, resulting in poor injection molding operability. In addition, the inorganic fillers may sometimes settle during curing, resulting in a difference in the linear expansion coefficient between the upper surface and the bottom surface of the cured product, so that the cured product of the sealing resin is prone to cracking, and the reliability of the resulting device is reduced.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2009-67890 Summary of the invention
[0009] Technical issues to be solved by the invention
[0010] The present invention is completed in view of the above-mentioned problems, and its purpose is to provide a liquid resin composition for sealing power semiconductor elements and a power device having the liquid resin composition as a sealing material. The above-mentioned liquid resin composition has low viscosity and reduces the sedimentation of inorganic fillers during storage, so it is excellent in injection molding operability, reduces the sedimentation of inorganic fillers during curing, and has excellent heat resistance. The above-mentioned power device has excellent crack resistance, electrical properties, mechanical properties and heat resistance.
[0011] Means for solving technical problems
[0012] According to the present invention, there are provided the following liquid resin composition and power device.
[0013] [1] A liquid resin composition for sealing a power module by injection molding, the power module comprising a power module substrate having a circuit layer formed thereon and a power semiconductor element mounted on the circuit layer of the power module substrate,
[0014] The liquid resin composition comprises (A) epoxy resin, (B) acid anhydride, (C) curing accelerator, (D) inorganic filler and (E) anti-settling agent.
[0015] The epoxy resin (A) comprises an alicyclic epoxy resin,
[0016] The viscosity of the liquid resin composition at 25° C. is 75 Pa·s or less.
[0017] [2] The liquid resin composition according to item [1], wherein the content of the inorganic filler (D) is 65% by mass or more and 85% by mass or less based on the total solid content of the liquid resin composition.
[0018] [3] The liquid resin composition according to item [1] or [2], further comprising core-shell type rubber particles.
[0019] [4] The liquid resin composition according to item [3], wherein the content of the core-shell type rubber particles is 0.1% by mass or more and 10% by mass or less based on the total solid content of the liquid resin composition.
[0020] [5] The liquid resin composition according to any one of items [1] to [4], further comprising a flame retardant.
[0021] [6] The liquid resin composition according to any one of items [1] to [5], wherein the flow distance determined under the following conditions is 20 mm or more.
[0022] Conditions: 0.05 ml of the liquid resin composition is applied on a glass plate in such a manner that the diameter of the liquid resin composition becomes less than 1 cm. Then, the glass plate is maintained at a temperature of 60°C at an inclined angle of 45° for 3 minutes. The distance the liquid resin composition flows during this period is set as the flow distance (mm).
[0023] [7] The liquid resin composition according to any one of items [1] to [6], wherein the amount of the alicyclic epoxy resin contained in the epoxy resin (A) is 75% by mass or more relative to the total amount of the epoxy resin (A).
[0024] [8] The liquid resin composition according to any one of items [1] to [7], wherein the epoxy resin (A) further comprises a liquid bisphenol A epoxy resin or a liquid bisphenol F epoxy resin.
[0025] [9] The liquid resin composition according to item [8], wherein the amount of the liquid bisphenol A epoxy resin or the liquid bisphenol F epoxy resin contained in the epoxy resin (A) is 25% by mass or less relative to the total amount of the epoxy resin (A).
[0026]
[10] The liquid resin composition according to any one of items [1] to [9], wherein the acid anhydride (B) comprises at least one selected from the group consisting of methyl-5-norbornene-2,3-dicarboxylic anhydride, methylcyclohexane-1,2-dicarboxylic anhydride and methyltetrahydrophthalic anhydride.
[0027]
[11] The liquid resin composition according to item
[10] , wherein the viscosity of the methyltetrahydrophthalic anhydride at 25°C is 30 mPa·s or more and 50 mPa·s or more.
[0028]
[12] The liquid resin composition according to any one of items [1] to
[11] , wherein the curing accelerator (C) comprises an organic acid salt of diazabicycloundecene.
[0029]
[13] The liquid resin composition according to any one of items [1] to
[12] , wherein the sedimentation inhibitor (E) comprises bentonite or a polyhydroxycarboxylic acid ester.
[0030]
[14] A resin-sealed power module comprising: a power module substrate having a circuit layer formed thereon; a power semiconductor element mounted on the circuit layer of the power module substrate; and a sealing material covering the power module substrate and the power semiconductor element,
[0031] The sealing material is formed from a cured product of the liquid resin composition according to any one of items [1] to
[13] .
[0032] Effects of the Invention
[0033] According to the present invention, a liquid resin composition for sealing a power semiconductor element and a power device having the liquid resin composition as a sealing material are provided. The liquid resin composition has low viscosity and excellent injection molding operability, reduces the sedimentation of the inorganic filler during curing, and has excellent heat resistance. The power device has excellent crack resistance, electrical properties, mechanical properties and heat resistance. DETAILED DESCRIPTION
[0034] Hereinafter, embodiments of the present invention will be described.
[0035] Wherein, in this specification, the numerical range represented by "~" represents the range including the numerical values recorded before and after "~" as the minimum and maximum values, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. "A or B" means that as long as any one of A and B is included, both can be included. Regarding the materials exemplified in this specification, unless otherwise specifically stated, one can be used alone or two or more can be used in combination. In this specification, regarding the content of each component in the composition, when there are multiple substances equivalent to each component in the composition, unless otherwise specifically stated, it means the total amount of the multiple substances present in the composition.
[0036] [Liquid resin composition]
[0037] The resin composition of the present embodiment is a liquid resin composition for injection molding for sealing a power semiconductor element. More specifically, the resin composition of the present embodiment is used to seal a power module by injection molding, wherein the power module has a power module substrate having a circuit layer formed thereon and a power semiconductor element mounted on the circuit layer of the power module substrate.
[0038] The liquid resin composition for power module injection molding of this embodiment (sometimes referred to as "resin composition" in this specification) includes (A) epoxy resin, (B) acid anhydride, (C) curing accelerator, (D) inorganic filler and (E) anti-settling agent. In this embodiment, the epoxy resin (A) includes alicyclic epoxy resin. In addition, the viscosity of the resin composition of this embodiment at 25°C is 75 Pa·s or less.
[0039] The viscosity of the resin composition of the present embodiment at 25°C is 75 Pa·s or less. Thus, the injection molding operability is excellent. In addition, the resin composition of the present embodiment includes the above-mentioned components (A) to (E), and the epoxy resin (A) includes an alicyclic epoxy resin. By using an alicyclic epoxy resin, the obtained resin composition has excellent heat resistance.
[0040] Hereinafter, the components used in the resin composition of the present embodiment will be described in detail.
[0041] (Epoxy resin (A))
[0042] The epoxy resin (A) contained in the resin composition of the present embodiment includes an alicyclic epoxy resin. The use of an alicyclic epoxy resin allows the obtained resin composition to have a high glass transition temperature of 200° C. or higher, and thus has heat resistance sufficient for use as a sealing material for a power module.
[0043] As the alicyclic epoxy resin used in the present embodiment, it is preferred to use an alicyclic epoxy resin that is liquid at 25° C. Examples of such liquid alicyclic epoxy resins include vinyl cyclopentadiene dioxide, vinyl cyclohexene monodioxide, vinyl cyclohexene dioxide, dicyclopentadiene oxide, 3,4-epoxy-1-[8,9-epoxy-2,4-dioxaspiro[5.5]undec-3-yl]-cyclohexane and other epoxy-[epoxy-oxaspiro[C] 8-15 alkyl]-ring C 5-12 Alkanes, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, 4,5-epoxycyclooctylmethyl-4',5'-epoxycyclooctanecarboxylate and other epoxy C 5-12 Cycloalkyl C 1-3 Alkyl-epoxy C 5-12 Cycloalkane carboxylate, bis(2-methyl-3,4-epoxycyclohexylmethyl) adipate, etc. 1-3 Alkyl Epoxide C 5-12 Cycloalkyl C 1-3 As a commercial product of 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, there can be mentioned CELLOXIDE#2021P (epoxy equivalent: 128 to 140) manufactured by Daicel Corporation, which is preferably used.
[0044] The amount of the alicyclic epoxy resin contained in the epoxy resin (A) is, for example, 70 mass % or more, preferably 75 mass % or more, and more preferably 80 mass % or more, based on the entire epoxy resin (A).
[0045] In a preferred embodiment, the epoxy resin (A) contains, in addition to the alicyclic epoxy resin, a bisphenol A epoxy resin or a bisphenol F epoxy resin. By using these epoxy resins, the heat resistance of the cured product of the obtained resin composition can be further improved, and the insulation reliability can be improved.
[0046] When the epoxy resin (A) contains a bisphenol A epoxy resin or a bisphenol F epoxy resin, the amount thereof is, for example, 30 mass % or less, preferably 25 mass % or less, and more preferably 20 mass % or less, based on the entire epoxy resin (A).
[0047] The epoxy resin (A) may contain other epoxy resins different from the above epoxy resins within the range that the physical properties of the cured product of the obtained resin composition, such as heat resistance and insulation, are not impaired. As other epoxy resins, for example, bisphenol E epoxy resin, bisphenol S epoxy resin, bisphenol M epoxy resin (4,4'-(1,3-phenylene diisopropylidene) bisphenol type epoxy resin), bisphenol P epoxy resin (4,4'-(1,4-phenylene diisopropylidene) bisphenol type epoxy resin), bisphenol Z epoxy resin (4,4'-cyclohexadiene bisphenol type epoxy resin) and other bisphenol type epoxy resins; phenol novolac type epoxy resin, cresol novolac type epoxy resin, trisphenol methane type novolac type epoxy resin, tetraphenol ethane type novolac type epoxy resin; Novolac epoxy resins such as lacquer epoxy resins and novolac epoxy resins having a condensed aromatic hydrocarbon structure; biphenyl epoxy resins; arylalkylene epoxy resins such as xylene epoxy resins and biphenylaralkyl epoxy resins; naphthalene ether epoxy resins, naphthol epoxy resins, naphthyldiol epoxy resins, difunctional to tetrafunctional epoxy-type naphthalene resins, binaphthyl epoxy resins, naphthalenearalkyl epoxy resins and other naphthalene epoxy resins; anthracene epoxy resins; phenoxy epoxy resins; dicyclopentadiene epoxy resins; norbornene epoxy resins; adamantane epoxy resins; fluorene epoxy resins, etc. When these epoxy resins are used, the amount thereof is, for example, 10% by mass or less, preferably 5% by mass or less, relative to the total amount of the epoxy resin (A).
[0048] The amount of the epoxy resin (A) in the resin composition of the present embodiment is, for example, 2% to 30% by mass, preferably 4% to 25% by mass, relative to the entire resin composition. In addition, the amount of the epoxy resin (A) in the resin composition refers to the total amount of the alicyclic epoxy resin and the bisphenol A epoxy resin or bisphenol F epoxy resin used as needed, or other epoxy resins.
[0049] (anhydride (B))
[0050] The resin composition of this embodiment contains an acid anhydride (B). The acid anhydride (B) functions as a curing agent for the epoxy resin (A). Examples of the acid anhydride (B) that can be used include dodecenylsuccinic anhydride, polyadipic anhydride, polyazelaic anhydride, polysebacic anhydride, poly(ethyloctadecanedioic acid) anhydride, poly(phenylhexadecanedioic acid) anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methyl NA anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylcyclohexene dicarboxylic anhydride, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol ditrimellitate, chlorobridged anhydride, tetrahydrophthalic anhydride, methyl nadic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride), methyl NA anhydride (methylhimic acid anhydride), tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylcyclohexene dicarboxylic anhydride, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol ditrimellitate, chlorobridged anhydride, tetrahydrophthalic anhydride, methyl nadic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride), methyl NA anhydride (methylhimic acid anhydride), Anhydride, methyl-3,6-endomethylene-1,2,3,6-tetrahydrophthalic anhydride), 4-methylcyclohexane-1,2-dicarboxylic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexane-1,2-dicarboxylic anhydride, etc. Among them, as the acid anhydride (B), methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride, methylcyclohexane-1,2-dicarboxylic anhydride, which are liquid anhydrides at 25° C., are preferably used because they can be easily mixed evenly with other components such as the epoxy resin (A). Among them, methyl-5-norbornene-2,3-dicarboxylic anhydride, methylcyclohexane-1,2-dicarboxylic anhydride and methyltetrahydrophthalic anhydride are particularly preferred. When methyltetrahydrophthalic anhydride is used, it is preferred to use a substance having a viscosity of 30 to 50 mPa·s at 25° C. By using such anhydride, the viscosity of the obtained resin composition can be further reduced. Examples of commercially available acid anhydrides include HN series manufactured by Showa Denko Materials Co., Ltd.
[0051] The acid anhydride (B) may be used alone or in combination of two or more.
[0052] From the viewpoint of operability and curability, the amount of the anhydride (B) in the resin composition of the present embodiment is preferably 10% to 60% by mass, more preferably 15% to 50% by mass, relative to the entire resin composition. In addition, the ratio of the total number of functional groups of the anhydride to the total number of epoxy groups of the epoxy resin (A) is preferably 0.7 to 1.2, more preferably 0.8 to 1.1. By using the anhydride (B) in an amount within the above range, the mechanical strength and insulation of the cured product of the obtained resin composition can be improved.
[0053] (Curing accelerator (C))
[0054] The resin composition of the present embodiment includes a curing accelerator (C). The curing accelerator (C) has the effect of promoting the reaction of the epoxy resin (A) and the acid anhydride (B) as a curing agent. As the curing accelerator (C) that can be used, tertiary amines, quaternary ammonium salts, imidazoles, organic phosphine, Lewis acid catalysts, etc. can be cited. Among them, quaternary ammonium salts are preferably used.
[0055] Examples of the tertiary amine include trimethylamine, triethylamine, tripropylamine, tributylamine, and benzyldimethylamine.
[0056] Examples of the quaternary ammonium salt include organic acid salts of diazabicycloundecene such as DBU [1,8-diazabicyclo[5.4.0]undecene-7] octanoate (manufactured by San-Apro Ltd., product name: SA102), DBN [1,5-diazabicyclo[4.3.0]-5-nonene], quaternary ammonium salts which are salts of tertiary amines and carboxylic acids (manufactured by San-Apro Ltd., product name: U-CAT2313), octadecyltrimethylammonium chloride (manufactured by NOF CORPORATION, product name: Nissan Cation), and tetraalkylammonium salts (each alkyl group having 1 to 18 carbon atoms) (e.g., tetraethylammonium bromide, tetrabutylammonium bromide, and tetraalkylammonium carboxylates (carboxylic acids having 1 to 12 carbon atoms)).
[0057] Examples of the imidazoles include 1-benzyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 1,2-dimethylimidazole, and 1-benzyl-2-phenylimidazole.
[0058] Examples of the organic phosphine include triphenylphosphine, triphenylphosphine-triphenylborate, tri(p-methoxyphenyl)phosphine, and tetraphenylphosphonium-tetraphenylborate.
[0059] Examples of the Lewis acid catalyst include boron trifluoride amine complex, boron trichloride amine complex, and boron trifluoride ethylamine complex.
[0060] These may be used alone or in combination of two or more.
[0061] The amount of the curing accelerator (C) in the resin combination of the present embodiment is, for example, more than 0.03 mass % relative to the entire resin combination, preferably more than 0.05 mass %, more preferably more than 0.08 mass %.Thus, the curability of the resin combination can be improved.On the other hand, the upper limit of the content of the curing accelerator (C) is, for example, less than 1 mass % relative to the entire resin combination, preferably less than 0.8 mass %, more preferably less than 0.5 mass %.Thus, the injection molding operability can be improved.
[0062] (Inorganic filler (D))
[0063] The resin composition of the present embodiment includes inorganic filler (D). As inorganic filler (D), silica fillers such as quartz, pyrogenic silica, sedimentation silica, silicic anhydride, fused silica, crystalline silica, ultrafine powder amorphous silica, aluminum oxide, zircon, iron oxide, zinc oxide, titanium oxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, glass fiber, glass sheet, aluminum oxide fiber, carbon fiber, mica, black lead, carbon black, ferrite, graphite, diatomaceous earth, white clay, clay, talc, aluminum hydroxide, magnesium hydroxide, calcium carbonate, manganese carbonate, magnesium carbonate, barium sulfate, potassium titanate, calcium silicate, inorganic hollow sphere, silver powder, etc. can be cited. These can be used alone, or two or more can be used simultaneously. In addition, the inorganic filler can be surface treated. As surface treatment, alkylation, trimethyl silylation, organosilicon treatment, treatment using a silane coupling agent, etc. can be cited, but it is not particularly limited.
[0064] By using the inorganic filler (D), the viscosity of the obtained resin composition can be adjusted to an appropriate range, and various physical properties such as strength, hardness, elastic modulus, thermal expansion coefficient, thermal conductivity, heat dissipation, and electrical characteristics of the cured product of the resin composition can be improved.
[0065] Among the inorganic fillers (D), silica fillers are preferably used. Silica fillers include silica-based fillers such as quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, and ultrafine amorphous silica.
[0066] In common resin composition, if the addition amount of filler increases, the viscosity of the resin composition comprising the filler obviously rises. About shape, from the viewpoint of controlling viscosity, compared with fibrous, amorphous shape, preferably spherical. Here, spherical can be a true sphere, or it can be an ellipsoid, representing a roughly spherical shape including oval, etc., specifically, aspect ratio (ratio of major diameter to minor diameter) is usually less than 1.3, preferably less than 1.2, more preferably less than 1.1.
[0067] Furthermore, from the viewpoint of compounding, it is preferred that the filler has a hydroxyl group on the surface. The presence of a hydroxyl group can increase the polarity of the filler surface, and thus it is easier to mix an organic polymer having a high polarity than an inorganic substance.
[0068] Furthermore, the amount of filler added can be increased by controlling the particle size distribution. That is, by mixing fillers with different particle sizes, a higher filling rate can be obtained.
[0069] The average particle size of the filler is measured using a Particle Size Analyzer (CILAS 1064) and is preferably 0.1 μm or more, more preferably 1 μm or more, and preferably 100 μm or less, more preferably 50 μm or less.
[0070] The amount of the inorganic filler (D) in the resin composition of the present embodiment is, for example, 65% to 85% by mass relative to the entire resin composition. The lower limit of the amount of the inorganic filler (D) is preferably 68% by mass or more relative to the entire resin composition, more preferably 70% by mass or more, and further preferably 75% by mass or more. The upper limit of the amount of the inorganic filler (D) is preferably 82% by mass or less relative to the entire resin composition, more preferably 80% by mass or less. By using the inorganic filler (D) in an amount within the above range, the resulting resin composition has a viscosity suitable for injection molding, so the injection molding operability is excellent, and the cured product of the resin composition has low thermal expansion and high heat resistance. Thus, the curability of the resin composition can be improved.
[0071] (Anti-settling agent (E))
[0072] The resin composition of the present embodiment contains an anti-settling agent (E). By using the anti-settling agent (E), the inorganic filler (D) can be inhibited from settling in the resin composition. As the anti-settling agent (E) that can be used, for example, micro-silica, asbestos powder, needle-shaped magnesium, polyhydroxycarboxylic acid esters, synthetic wax, ultra-fine precipitated calcium carbonate, clay, talc, organic bentonite, metal soaps, plant-based polymerized oils, oxidized polyethylene-based surfactants, etc. can be cited.
[0073] The amount of the anti-settling agent (E) in the resin composition of the present embodiment is, for example, 0.01% to 1.00% by mass relative to the resin composition as a whole. The lower limit of the amount of the anti-settling agent (E) is preferably 0.05% by mass or more relative to the resin composition as a whole, and more preferably 0.10% by mass or more. The upper limit of the amount of the anti-settling agent (E) is preferably 0.80% by mass or less relative to the resin composition as a whole, and more preferably 0.50% by mass or less. By using the anti-settling agent (E) in an amount within the above range, the filler sedimentation of the obtained resin composition during storage and curing is suppressed, and the viscosity and fluidity suitable for injection molding operability can be maintained.
[0074] (Core-shell rubber particles)
[0075] The resin composition of the present embodiment may include core-shell rubber particles. By using core-shell rubber particles, the bending elastic modulus of its cured product can be reduced without a significant increase in the viscosity of the liquid resin composition. Therefore, a resin composition having good operability and capable of forming a cured product having high strength and low elastic modulus can be obtained.
[0076] Core-shell rubber particles are rubber particles in which a particulate core component mainly composed of a crosslinked rubber polymer is graft-polymerized onto the surface of the core component to cover part or all of the surface of the core component with a shell component.
[0077] As the core component, for example, crosslinked rubber particles can be cited. As crosslinked rubber particles, diene rubber, acrylic rubber and polysiloxane rubber can be cited. More specifically, butadiene rubber, acrylic rubber, silicone rubber, butyl rubber, nitrile rubber, styrene rubber, synthetic natural rubber, ethylene propylene rubber and the like can be cited.
[0078] As the shell component, for example, diene rubber, acrylic rubber and polysiloxane rubber can be cited. Preferably, a polymer formed by polymerization of one or more monomers selected from acrylate, methacrylate and aromatic vinyl compound is cited. In addition, it is preferred that the shell component is graft polymerized with the core component and chemically bonded to the polymer constituting the core component. In addition, in the case of using a cross-linked rubber-like polymer composed of a polymer of styrene and butadiene as the core component, it is preferred to use a polymer of methyl methacrylate as methacrylate and styrene as an aromatic vinyl compound as the shell component.
[0079] Examples of commercially available core-shell rubber particles include “PARALOID (registered trademark)” EXL-2655 (manufactured by Kureha Chemical Co., Ltd.) composed of a butadiene-alkyl methacrylate-styrene copolymer, “STAFILOID (registered trademark)” AC-3355 and TR-2122 (manufactured by Takeda Pharmaceutical Co., Ltd.) composed of an acrylate-methacrylate copolymer, “PARALOID (registered trademark)” EXL-2611 and EXL-3387 (manufactured by Rohm & Haas Company) composed of a butyl acrylate-methyl methacrylate copolymer, and “KaneAce (registered trademark)” MX series (manufactured by Kaneka Corporation).
[0080] The core-shell rubber particles can also be obtained in the form of a masterbatch of epoxy resin pre-dispersed in an epoxy resin. Examples of such core-shell rubber particle-dispersed epoxy resins include "KaneAce (registered trademark)" (manufactured by Kaneka Corporation) and "ACRYSET (registered trademark) BP series" (manufactured by Nippon Shokubai Co., Ltd.).
[0081] By dispersing the epoxy resin using such a masterbatch type core-shell type rubber particle, the dispersion state of the core-shell type rubber particles in the obtained resin composition can be improved.
[0082] As commercially available products of core-shell rubber particle-dispersed epoxy resins, MX-113, MX-120, MX-125, MX-128, MX-130, MX-135, MX-136, MX-156, MX-153, MX-257, MX-150, MX-154, MX-960, MX-170, MX-267, MX-965, MX-217, MX-416, MX-451, MX-553, MX-710, MX-714, etc. of the MX series of KaneAce manufactured by Kaneka Corporation can be used.
[0083] From the viewpoint of obtaining a resin composition capable of forming a cured product having high strength and low elastic modulus, the content of the core-shell rubber particles is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, based on the total solid content of the resin composition.
[0084] Furthermore, from the viewpoint of obtaining a resin composition capable of forming a cured product having high strength and low elastic modulus, the average particle size of the primary particles of the core-shell type rubber particles is preferably in the range of 50 to 500 nm, more preferably in the range of 50 to 300 nm.
[0085] The resin composition of the present embodiment may contain a flame retardant. By using a flame retardant, a resin composition capable of forming a cured product having high flame retardancy can be obtained. As flame retardants that can be used in the resin composition of the present embodiment, for example, aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, antimony trioxide, antimony pentoxide, phosphazene, brominated epoxy resin, brominated polycarbonate, etc. can be cited. One flame retardant can be used alone, or two or more flame retardants can be used in combination.
[0086] When a flame retardant is used, its amount is, for example, 1 to 50% by mass, preferably 5 to 30% by mass, relative to the entire resin composition. By using a flame retardant in an amount within the above range, the obtained liquid resin composition can be maintained at a viscosity and fluidity suitable for injection molding operability, and the flame retardancy of the obtained cured product can be improved.
[0087] (Coupling agent)
[0088] The resin composition of the present embodiment may contain a coupling agent. By using a coupling agent, the compatibility between the epoxy resin (A) and the inorganic filler (D) can be improved.
[0089] Examples of the coupling agent that can be used include silane coupling agents such as epoxysilane, aminosilane, ureidosilane, and mercaptosilane.
[0090] Examples of the epoxysilane include γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. Furthermore, examples of aminosilanes include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl) γ-aminopropyltrimethoxysilane, N-β (aminoethyl) γ-aminopropylmethyldimethoxysilane, N-phenyl-γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, N-β (aminoethyl) γ-aminopropyltriethoxysilane, N-(6-aminohexyl) 3-aminopropyltrimethoxysilane, and N-(3-(trimethoxysilylpropyl)-1,3-phenylenediamine. Further, examples of ureidosilanes include γ-ureidopropyltriethoxysilane and hexamethyldisilazane. These may be used alone or in combination of two or more.
[0091] As the lower limit of the content of coupling agent, relative to the whole resin combination, for example, more than 0.05 mass %, preferably more than 0.02 mass %, more preferably more than 0.05 mass %. As the upper limit of the content of coupling agent, relative to the whole resin combination, for example, less than 1 mass %, preferably less than 0.8 mass %, more preferably less than 0.6 mass %. Thus, it is possible to suppress the reduction of the interfacial strength of epoxy resin (A) and inorganic filler (D), so the obtained resin combination has excellent durability.
[0092] (Other additives)
[0093] The resin composition of the present embodiment may contain a colorant such as carbon black, or a defoaming agent such as a silicone defoaming agent, as necessary.
[0094] (Method for producing liquid resin composition)
[0095] The method for producing the liquid resin composition according to the present embodiment will be described in detail.
[0096] The resin composition of this embodiment can be produced by adding the above-mentioned components, namely, epoxy resin (A), acid anhydride (B), curing accelerator (C), inorganic filler (D), anti-settling agent (E) and other components by conventional methods and thoroughly mixing and stirring.
[0097] In one embodiment, the resin composition of the present invention can be obtained by mixing and / or kneading a main agent component and a curing agent component. More specifically, for example, a part of an inorganic filler (D), an anti-settling agent (E) and various components prepared as needed are mixed in an epoxy resin (A) to manufacture a main agent component. In addition, a curing accelerator (C), the remainder of an inorganic filler (D), an anti-settling agent (E) and various components prepared as needed are mixed in an anhydride (B) as a curing agent to manufacture a curing agent component. Then, a mixing machine such as a mixer or a kneading machine, a roller and the like are used to mix and / or knead the main agent component and the curing agent component to obtain a liquid resin composition.
[0098] (Physical Properties of Liquid Resin Composition)
[0099] The resin composition of the present embodiment is characterized in that it is in a liquid state at 25° C., which makes injection molding easy and is less likely to be thermally cured.
[0100] The viscosity of the liquid resin composition of the present embodiment containing the above-mentioned components at 25°C is 75 Pa·s or less, preferably 70 Pa·s or less, more preferably 65 Pa·s or less, further preferably 60 Pa·s or less, and further preferably 55 Pa·s or less. The lower limit of the viscosity of the resin composition at 25°C is not particularly limited, for example, it is 5 Pa·s or more. The liquid resin composition having the viscosity in the above range has excellent injection molding operability.
[0101] The flow distance of the liquid resin composition of the present embodiment obtained under the following conditions is preferably more than 20 mm, more preferably more than 25 mm, further preferably more than 30 mm, and further preferably more than 35 mm. The upper limit of the flow distance of the resin composition is, for example, less than 80 mm. The liquid composition with a flow distance in this range has excellent injection molding operability.
[0102] (Conditions) 0.05 ml of the liquid resin composition of the present embodiment is applied on a glass plate so that the diameter of the liquid resin composition is 1 cm or less. Next, the glass plate is kept at a temperature of 60° C. at an inclined angle of 45° for 3 minutes, and the distance the liquid resin composition flows during this period is defined as the flow distance (mm).
[0103] (Method for curing resin composition)
[0104] The heating method for curing the resin composition of this embodiment is not particularly limited, and for example, conventionally known methods such as hot air circulation heating, infrared heating, and high-frequency heating can be used. There are no particular restrictions on the heat treatment conditions as long as the resin composition can be cured as expected, and for example, a temperature of 100°C to 200°C can be used. (Physical Properties of Cured Resin Composition)
[0105] The cured product of the liquid resin composition of the present embodiment has a glass transition temperature of 180°C or more, preferably 190°C or more, more preferably 200°C or more, further preferably 205°C or more, and particularly preferably 210°C or more. As a result, the cured product of the liquid resin composition has excellent heat resistance and is therefore suitable for use as a sealing material for a power module. The upper limit of the glass transition temperature of the cured product of the resin composition of the present embodiment is, for example, 250°C or less.
[0106] The cured product of the liquid resin composition of the present embodiment has a linear expansion coefficient of 25 ppm / K or less, preferably 20 ppm / K or less, and more preferably 15 ppm / K or less. Thus, the cured product of the liquid resin composition has excellent crack resistance. The lower limit of the linear expansion coefficient of the cured product of the liquid resin composition of the present embodiment is, for example, 10 ppm / K or more.
[0107] The flexural modulus of the cured product of the liquid resin composition of the present embodiment at 25° C. is, for example, 20 GPa or less, preferably 18 GPa or less, and more preferably 16 GPa or less. The lower limit of the flexural modulus of the cured product of the resin composition of the present embodiment at 25° C. is, for example, 10 GPa or more.
[0108] [Power Module]
[0109] The cured product of the resin combination of the present embodiment has a low coefficient of thermal expansion at high temperatures, and has high heat resistance, and is therefore suitable for use as a sealing material for power modules. As power modules, for example, rectifiers, frequency converters, regulators, inverters, etc. can be cited. The resin combination of the present invention has fluidity as a resin combination, so injection molding operability is good. In addition, the cured product of the resin combination of the present embodiment has a low coefficient of linear expansion, and is therefore suitable for power modules of various sizes. It can also be used for power modules of household appliances, computers, etc., and can also be used for large power modules for control of automobiles, railway vehicles, or transformer substations, etc.
[0110] The power module of the present embodiment can be obtained by injection molding the above-mentioned resin composition in a manner of covering these substrates and power semiconductor elements on a power module substrate formed with a circuit layer, and curing it. Preferably, the resin composition is vacuum degassed during injection molding and / or before and after injection molding. By performing vacuum degassed, the air contained in the resin composition can be removed, and a resin-sealed power module with few pores in the cured product of the epoxy resin composition can be obtained. The power module of the present embodiment has the cured product of the above-mentioned resin composition as a sealing material, and thus has excellent reliability.
[0111] As mentioned above, although embodiment of this invention was demonstrated, these are illustrations of this invention, and various structures other than the above-mentioned can also be adopted.
[0112] Example
[0113] Hereinafter, the present invention will be described by way of Examples and Comparative Examples, but the present invention is not limited thereto.
[0114] The raw materials used in Examples and Comparative Examples are as follows.
[0115] <(A) Epoxy resin>
[0116] Epoxy resin 1: Cycloaliphatic epoxy resin (manufactured by Daicel Corporation, CELLOXIDE 2021P)
[0117] · Epoxy resin 2: Bisphenol A type epoxy resin (Mitsubishi Chemical Corporation, jER828EL) <(B) Acid anhydride (curing agent)>
[0118] Acid anhydride 1: Methylnadic anhydride (manufactured by Showa Denko Materials Co., Ltd., MHAC-P)
[0119] Acid anhydride 2: Methylhexahydrophthalic anhydride (manufactured by Showa Denko Materials Co., Ltd., HN-5500)
[0120] Acid anhydride 3: Methyltetrahydrophthalic anhydride (manufactured by Showa Denko Materials Co., Ltd., HN-2000)
[0121] <(C) Curing accelerator>
[0122] Curing accelerator 1: DBU-octanoate (manufactured by San-Apro Ltd., U-CAT SA102)
[0123] Curing accelerator 2: DBU-phenolate (manufactured by San-Apro Ltd., U-CAT SA1)
[0124] <(D) Inorganic fillers>
[0125] Inorganic filler 1: spherical fused silica (manufactured by Denka Company Limited., FB-950, volume average particle size: 23 μm)
[0126] <(E) Sedimentation inhibitor>
[0127] · Sedimentation inhibitor 1: Organic bentonite (S-BEN N-400, manufactured by Fengshun Co., Ltd.)
[0128] · Sedimentation inhibitor 2: Polyhydroxycarboxylic acid ester (BYK Chemie Japan, BYK-R606) <(F) Flame retardant>
[0129] Flame retardant 1: Brominated epoxy resin (Epiclon 153, manufactured by DIC)
[0130] Flame retardant 2: Antimony trioxide (PATOX-K, manufactured by Nippon Seiko Co., Ltd.)
[0131] Flame retardant 3: Aluminum hydroxide (manufactured by Sumitomo Chemical Co., Ltd., CWL-325J)
[0132] <Other additives>
[0133] · Low stress agent 1: core-shell rubber particles (MX-553 manufactured by Kaneka Corporation, core-shell rubber particle dispersed epoxy resin having a mass ratio of 7:3 of alicyclic epoxy resin (CELLOXIDE 2021P):core-shell rubber particles)
[0134] Colorant 1: Carbon black (Mitsubishi Chemical Corporation, Carbon #5)
[0135] · Coupling agent 1: Epoxy silane coupling agent (Momentive Performance Materials Inc., A-187)
[0136] Defoamer 1: Silicone defoamer (KS603, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0137] (Example 1 to Example 20, Comparative Example 1 to Comparative Example 2)
[0138] <Production of liquid resin composition>
[0139] The components shown in the "main agent" of Table 1 were mixed in the amounts shown in Table 1 to obtain a main agent (I). In addition, the components shown in the "curing agent" of Table 1 were mixed in the amounts shown in Table 1 to obtain a curing agent (II). 100 parts by mass of the main agent (I) and 100 parts by mass of the curing agent (II) were mixed to prepare a liquid resin composition.
[0140] <Evaluation of physical properties of liquid resin composition>
[0141] The following physical properties were measured for the liquid resin compositions obtained in the respective Examples and Comparative Examples.
[0142] (Viscosity at 25°C)
[0143] The viscosity of the liquid resin composition was measured using an E-type viscometer and a rotor No. 4 at a rotation speed of 10 rpm, a temperature of 25° C., and a measurement time of 1 minute.
[0144] (Liquidity)
[0145] 0.05 ml of the liquid resin composition was applied to a glass plate so that the diameter of the liquid resin composition was less than 1 cm. Then, the glass plate was kept at a temperature of 60°C at an inclined angle of 45° for 3 minutes, and the distance the liquid resin composition flowed during this period was set as the flow distance (mm) and measured. The flow distance is shown in Table 1.
[0146] (Preservability)
[0147] The storage stability of the main agent (I) and the curing agent (II) was evaluated according to the following method.
[0148] First, the main agent (I) was placed in a 120 mL plastic container with a lid to a height of 50 to 55 mm, and the lid was closed. The height of the filler sediment (hard cake) accumulated at the bottom after 60°C × 24 hours was measured. If the height of the hard cake was 0 mm, it was recorded as "A"; if it was more than 0 mm and less than 3 mm, it was recorded as "B"; if it was 3 mm or more, it was recorded as "C", which is shown in Table 1.
[0149] The storage stability of the curing agent (II) was evaluated in the same manner as that of the main agent (I).
[0150] (Injection molding operability)
[0151] The injection molding workability of the liquid resin composition was evaluated according to the following evaluation criteria.
[0152] A: All of the following (requirements 1) to (requirements 3) are met.
[0153] B: Satisfy any two of the following (requirements 1) to (requirements 3).
[0154] C: Satisfies any one of the following (requirements 1) to (requirements 3), or satisfies none of them.
[0155] Requirement 1: The viscosity of the liquid resin composition at 25° C. is 75 Pa·s or less.
[0156] Requirement 2: The flow distance in the fluidity evaluation of the liquid resin composition is 30 mm or more.
[0157] Requirement 3: As a result of the above storage stability evaluation, both the main agent (I) and the curing agent (II) were "A".
[0158] <Evaluation of physical properties of cured resin>
[0159] The following physical properties were measured for the cured products obtained by curing the liquid resin compositions obtained in the respective Examples and Comparative Examples.
[0160] (Glass transition temperature)
[0161] The liquid resin composition was injection molded into an aluminum cup and cured at 160°C for 1 hour and then at 180°C for 2 hours. After slowly cooling to room temperature, the test piece was cut into a size of 10 mm × 5 mm × 5 mm. A thermomechanical analyzer (TMA7100, manufactured by Hitachi High-Tech) was used to measure the test piece at a measurement temperature range of 0°C to 320°C and a heating rate of 10°C / min. And, the glass transition temperature (°C) was calculated based on the measurement results. The higher the glass transition temperature, the better the heat resistance of the cured product.
[0162] (Linear expansion coefficient)
[0163] The cured product of the resin composition obtained in each example was placed in a thermomechanical analyzer (manufactured by Hitachi High-Technologies, TMA7100) and measured under the conditions of a temperature range of 0°C to 320°C and a heating rate of 10°C / minute. The measured data was analyzed to determine the average linear expansion coefficient in the temperature range of 50°C to 70°C. The unit of the average linear expansion coefficient is [ppm / K]. The smaller the value of the average linear expansion coefficient, the lower the expansion of the cured product.
[0164] (Flexural modulus)
[0165] The resin composition obtained in each example was poured into an empty mold with a hole (width 4 mm, length 100 mm, height 120 mm), and cured at 160° C. for 1 hour and then at 180° C. for 2 hours. After slowly cooling to room temperature, the pieces were cut into a size of 4 mm×10 mm×100 mm, and the bending modulus at 25° C. was measured in accordance with JIS6911. The smaller the value of the bending modulus, the lower the elasticity of the cured product.
[0166] (Flame retardancy)
[0167] The resin composition obtained in Example 16 to Example 20 was poured into an empty mold with a hole (width 1.5 to 6.0 mm, length 100 mm, height 140 mm), and cured at 160°C for 1 hour, followed by 180°C for 2 hours. After slowly cooling to room temperature, the sample was cut into a size of 1.5 to 6.0 mm × 12.5 mm × 125 mm, and evaluated by burning time based on the UL-94 vertical test. Samples with a maximum burning time of less than 10 seconds and a total burning time of less than 50 seconds were evaluated as "V-0", and samples with a maximum burning time of less than 30 seconds and a total burning time of less than 250 seconds were evaluated as "V-1", as shown in Table 1.
[0168] Table 1
[0169]
[0170] Table 1 (continued)
[0171]
[0172] Table 1 (continued)
[0173]
[0174] The resin composition of the embodiment has a low viscosity, and therefore has excellent injection molding operability. The cured product of the resin composition of the embodiment is a material having a high glass transition temperature and low thermal expansion, and therefore is suitable for use as a sealing material having excellent heat resistance and crack resistance. Among them, the resin compositions of Embodiments 12 to 15, which particularly contain core-shell rubber particles, have a low viscosity, and their cured products have low elasticity. And, among them, the resin compositions of Embodiments 16 to 20, which contain flame retardants, have a low viscosity and excellent handleability, and their cured products have excellent flame retardancy.
[0175] This application claims the benefit of priority based on Japanese Patent Application No. 2022-090311 filed on June 2, 2022 and Japanese Patent Application No. 2023-016277 filed on February 6, 2023, and all the contents disclosed therein are incorporated herein by reference.
Claims
1. A liquid resin composition for sealing a power module by injection molding, wherein the power module comprises a power module substrate having a circuit layer formed thereon and a power semiconductor element mounted on the circuit layer of the power module substrate, wherein the liquid resin composition is characterized in that: The invention comprises (A) an epoxy resin, (B) an acid anhydride, (C) a curing accelerator, (D) an inorganic filler material and (E) an anti-settling agent, The epoxy resin (A) comprises an alicyclic epoxy resin, The viscosity of the liquid resin composition at 25° C. is 75 Pa·s or less.
2. The liquid resin composition according to claim 1, characterized in that The content of the inorganic filler (D) is 65% by mass or more and 85% by mass or less based on the total solid content of the liquid resin composition.
3. The liquid resin composition according to claim 1 or 2, characterized in that Also included are core-shell rubber particles.
4. The liquid resin composition according to claim 3, characterized in that The content of the core-shell type rubber particles is 0.1% by mass or more and 10% by mass or less based on the entire solid content of the liquid resin composition.
5. The liquid resin composition according to any one of claims 1 to 4, characterized in that Also contains flame retardants.
6. The liquid resin composition according to any one of claims 1 to 5, characterized in that The flow distance obtained under the following conditions is 20 mm or more. Conditions: 0.05 ml of the liquid resin composition is applied on a glass plate in such a manner that the diameter of the liquid resin composition becomes less than 1 cm. Then, the glass plate is maintained at a temperature of 60°C at an inclined angle of 45° for 3 minutes. The distance the liquid resin composition flows during this period is set as the flow distance (mm).
7. The liquid resin composition according to any one of claims 1 to 6, characterized in that The amount of the alicyclic epoxy resin contained in the epoxy resin (A) is 75% by mass or more based on the entire epoxy resin (A).
8. The liquid resin composition according to any one of claims 1 to 7, characterized in that The epoxy resin (A) further comprises liquid bisphenol A epoxy resin or liquid bisphenol F epoxy resin.
9. The liquid resin composition according to claim 8, characterized in that The amount of the liquid bisphenol A epoxy resin or the liquid bisphenol F epoxy resin contained in the epoxy resin (A) is 25% by mass or less based on the entire epoxy resin (A).
10. The liquid resin composition according to any one of claims 1 to 9, characterized in that The acid anhydride (B) includes at least one selected from the group consisting of methyl-5-norbornene-2,3-dicarboxylic anhydride, methylcyclohexane-1,2-dicarboxylic anhydride, and methyltetrahydrophthalic anhydride.
11. The liquid resin composition according to claim 10, characterized in that The viscosity of the methyltetrahydrophthalic anhydride at 25° C. is 30 mPa·s or more and 50 mPa·s or more.
12. The liquid resin composition according to claim 1, characterized in that The curing accelerator (C) comprises an organic acid salt of diazabicycloundecene.
13. The liquid resin composition according to any one of claims 1 to 12, characterized in that The sedimentation inhibitor (E) comprises bentonite or polyhydroxycarboxylic acid ester.
14. A resin sealed power module, characterized in that: have: A power module substrate having a circuit layer formed thereon; a power semiconductor element mounted on the circuit layer of the power module substrate; and a sealing material covering the power module substrate and the power semiconductor element, The sealing material is formed of a cured product of the liquid resin composition according to any one of claims 1 to 13.
Citation Information
Patent Citations
Filler for semiconductor sealant and semiconductor sealant composition
JP2009067890A
Apparatus, method, and program
JP2022090311A
Game machine
JP2023016277A